Influence of Gender and Social Setting on College Student Food Choices - Kaela Giles; Magdalena Sas Ph.D; Jeannette Davidson (Undergraduate Research Journal for the Human Sciences, 2016)
To examine the effect of gender and social setting on food choices of college students in on-campus dining facilities. Healthiness of food choices was assessed by total calories, discretionary calories, and balance of food on lunch trays.
Keywords: College; Food